Pengaruh Tingkat Kesadaran Wajib Pajak, Pemahaman Aturan Perpajakan dan Sosialisasi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Cianjur - Assaja'ah, Aas; Khotimah, Husnul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This research endeavors to explore how well taxpayer awareness, comprehension of tax laws, and tax-related community programs impact individual taxpayer adherence within the KPP Pratama Cianjur jurisdiction.The methodological framework employed in this investigation is the quantitative approach. The study's population is comprised of individual taxpayers who are actively registered at KPP Pratama Cianjur. A sample group of 100 respondents was chosen using probability sampling methods, which involved conducting a survey by disseminating questionnaires. The data underwent analysis utilizing multiple regression techniques, employing the Ordinary Least Squares (OLS) method, and was processed through Stata software, version 17. The analytical results reveal that taxpayer awareness, knowledge of tax laws, and tax-related community programs are all variables that have a noteworthy impact on taxpayer compliance, both when considered together and when each is considered separately. Amongst these three variables, it is the grasp of tax regulations that stands out as exerting the most substantial influence on taxpayer compliance. This outcome underscores the need for enhanced initiatives in tax education and public awareness campaigns, highlighting them as vital steps towards elevating taxpayer compliance levels going forward.